Functional Outcomes of Close Reduction With K-wires Vs Open Reduction and Internal Fixation in Distal Radius Fractures - Dr Saddam Mazar; Dr M. Idrees Shah; Dr Shahbaz Khan Panhwar; Dr Syed Atta ur Rahman; syeda Laibah ali (ziauddin University, 2024)
Background: Radius and/or ulna fractures are frequent which encounter higher emergency room visits. Despite high incidence, proper management between closed reduction and internal fixation (CRIF) with K-wires and open reduction and internal fixation (ORIF) with anatomical Volar locking plate, remains debatable. This study aimed to compare the functional outcomes between the two management protocols. Methods: A total of 118 patients with distal radius fractures were treated operatively, at Dr. Ziauddin University Hospital Karachi, from January 2017 to October 2020. Out of these, 29 patients (24.6%) were treated with CRIF and 89 patients (75.4%) with ORIF. The functional outcomes of both groups were assessed through disabilities of arm, shoulder and hand (DASH) scores at 3 and 6 months. functional outcomes were assessed through a t-test, p-value <0.05 was considered significant. Results: The male to female ratio was 2.5:1, with an average age of 40.9 years. The Arbeitsgemeinschaft für Osteosynthesefragen (AO) 23-B type injury was observed in 29 (24.6%) patients. The mean DASH score among the ORIF group and CRIF group at 3 months was 43.03 and 46.19 (p <0.007) respectively. Whereas the DASH score of the ORIF and CRIF group at 6 months was 41.35 and 44.70 (p <0.007) respectively. Both groups at 6 months of management reported 33 (28%) patients with complete satisfaction, however, the return to work in the ORIF group was found highly significant (p=0.00). Conclusion: Open reduction and internal fixation with the distal radius locking compression plate produce functionally improved outcomes compared to K-wires for displaced distal radius fractures. Keywords: Radius, Bone Wires; Open Fracture Reduction; Fracture Fixation.